2014
DOI: 10.1149/2.0691414jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Corrosion Study of Metallic Materials in Phosphoric Acid as Bipolar Plates for HT-PEFCs

Abstract: This work investigates various commercially available austenitic stainless steels and Ni-based alloys as possible metallic bipolar plates for high-temperature polymer electrolyte fuel cells (HT-PEFCs). The dynamic formation and depletion of passivation layers that depends strongly on applied potential was analyzed in 85 wt% phosphoric acid at RT and 130 • C by means of cyclic voltammetry and steady-state polarization. All materials showed a beneficial passivation in the potential window 0.3-1.2 V, which is mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…First, the cathode side sample might be considered to be passivated and protected but the anode side samples not. This is in agreement with the findings from the electrochemical studies on a range of austenitic steels and nickel‐based alloys done by Weissbecker et al 5, in 85% H 3 PO 4 at 130 °C. They found that passivation (formation of protective oxide) was more prone to occur at cathodic potential (0.6 V) than at anodic potential (0 V).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…First, the cathode side sample might be considered to be passivated and protected but the anode side samples not. This is in agreement with the findings from the electrochemical studies on a range of austenitic steels and nickel‐based alloys done by Weissbecker et al 5, in 85% H 3 PO 4 at 130 °C. They found that passivation (formation of protective oxide) was more prone to occur at cathodic potential (0.6 V) than at anodic potential (0 V).…”
Section: Discussionsupporting
confidence: 93%
“…HTPEMFCs have therefore lower risk of cathode side flooding and allow the utilization of reformate fuels 4. At present HTPEM stacks are usually constructed with graphite bipolar plates and the use of metallic (steel) bipolar plates (BPPs) in contrast has only been recently discussed 5. Metallic bipolar plates offer the advantages of lower weight and volume, lower costs and better protection against phosphoric acid migration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, metallic BPPs have also been considered, particularly for LT-PEMFCs, due to their lower cost, lower weight and volume (especially when thin films are used), and an easier manufacture than graphitebased ones [31,32]. For HT-PEMFCs, the use of metallic BPPs has only been recently considered [18,[33][34][35][36][37][38]. HT-PEMFCs present a more corrosive environment in comparison to LT-PEMFCs, due to the higher temperature of operation, that enhances corrosion processes in acidic environments.…”
Section: Introductionmentioning
confidence: 99%
“…Metallic BPPs are considered a promising alternative for HT-PEMFCs, in order to minimize the effects of phosphoric acid up-take, as well as to reduce the total weight and cost of the stack [34,38]. Some authors have studied stainless steel BPPs, coated with different materials to increase their resistance to corrosion like Au, Ni, etc [30,34,35].…”
Section: Introductionmentioning
confidence: 99%